2016
DOI: 10.1590/0104-530x2288-15
|View full text |Cite
|
Sign up to set email alerts
|

Otimização da programação da produção de bebidas à base de frutas por meio de modelos de programação inteira mista

Abstract: ResumoNeste estudo, considera-se um problema de dimensionamento e programação de lotes de produção de bebidas não alcoólicas à base de frutas. O problema é caracterizado por horizonte de planejamento com múltiplos períodos, processo de produção com máquinas distintas, restrições de capacidades de produção e tempos de preparação das máquinas independentes da sequência de produção, além de condições especiais de preparações, como limpezas obrigatórias das máquinas dentro de limitações de tempo de produção. Para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Sanches et al [17] applied a multi-period MIP model for the optimization of production scheduling of fruit beverages. A case study in Brazil was used for validation of the proposed approach.…”
Section: Related Workmentioning
confidence: 99%
“…Sanches et al [17] applied a multi-period MIP model for the optimization of production scheduling of fruit beverages. A case study in Brazil was used for validation of the proposed approach.…”
Section: Related Workmentioning
confidence: 99%
“…Baldo et al [10] considered lot-sizing and scheduling in the brewery industry and developed a MIP-based heuristic to solve real-world problem instances. Pagliarussi et al [6] developed a MIP model to solve lot-sizing and scheduling problems of fruit juice beverage production of small-scale dimensions (the CPLEX solver was not capable of obtaining solutions within an acceptable computational time for most test instances). Toledo et al [8] developed the GA model that was compared to the exact model developed in the CPLEX solver to solve a synchronized and integrated two-level lot-sizing and scheduling problem (SITLSP) in soft drink production.…”
Section: Introductionmentioning
confidence: 99%
“…The authors developed two variants of a two-phase heuristic algorithm based on MIP and constructive heuristics. All of the papers from the soft drink production lot-sizing and scheduling research area [3,[5][6][7][8][9][10] observed the three segments in the objective function (inventories, backorder, production setup). A comparative analysis of relevant research papers addressing the similar problem observed in this paper, with research gaps, is presented in Table 2.…”
Section: Introductionmentioning
confidence: 99%
“…Com o notável crescimento da produção de bebidas não alcoólicas no Brasil nos últimos anos torna-se necessária a existência de maneiras mais eficientes de organização da produção e maior eficiência do cronograma de funcionamento de maquinários, aumentando a produtividade das indústrias (PAGLIARUSSI; MORABITO;SANTOS, 2016). O crescimento do número de fábricas de pequeno e médio porte levou a uma maior concorrência e crescente exigência de qualidade na categoria.…”
Section: Introductionunclassified